Supporting Open Peer Review And Preprint Adoption in Africa - Munene, Aurelia; Havemann, Jo (My University, 2023)
Presentation held at the OASPA 2023 Conference during the panel Preprints: Supporting Open Peer Review and Global Preprint Adoption Trends.
Keywords: Open Peer Review; Preprint Adoption; African Scientists